TÜRKİYE-LIBYA RELATIONS: TÜRKİYE’s EASTERN MEDITERRANEAN POLICY - Ahmet Burak (Bezbednosni Dijalozi)
Without a doubt, Türkiye is one of the most important Mediterranean powers and has made a significant contribution to the creation of Mediterranean culture for many centuries. And since the Justice and Development Party (tur. Adalet ve KalkınmaPartisi, AKP) came to power in 2002, Türkiye has made significant progress in strengthening the status of a regional power. When the intervention of the NATO military coalition in Libya started(March 19, 2011), which led to the fall of the government of Muammar Gaddafi. Thereby, Libya has become the scene of a civil war and a clash of geopolitical interests. It should be noted that Libya is an Ottoman heritage. This country is a familiar territory for Türkiye: for over 350 years, Libya was part of the Ottoman Empire. In connection with this today Ankara is actively involved in the conflict in Libya and increasing its presence in the Eastern Mediterranean. The article is devoted to Türkiye’s foreign policy at the present stage. Author in this study analysis that relations between Türkiye and Libya also Türkiye’s activities in the region within the sphere of its geopolitical interests in the Eastern Mediterranean are carried out at the political, economic, cultural and military.